2014
DOI: 10.1128/jvi.01558-14
|View full text |Cite
|
Sign up to set email alerts
|

Acute Clearance of Human Metapneumovirus Occurs Independently of Natural Killer Cells

Abstract: Human metapneumovirus (HMPV) is a major cause of respiratory disease. The role of NK cells in protection against HMPV is unclear. We show that while HMPV-infected C57BL/6 mice had higher numbers of functional lung NK cells than mock-treated mice, comparing NK cell-depleted and control mice did not reveal differences in lung viral titers, histopathology, cytokine levels, or T cell numbers or function. These data indicate that NK cells are not required for host control of HMPV. Human metapneumovirus (HMPV) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Several studies show that cotton rats are the most permissive small animal model and that peak virus titers occurred at day four post infection 76 78 . Viral lung replication and disease vary between different inbred mouse strains; most work has been published in the BALB/c model, which exhibits substantial disease symptoms 79 88 . BALB/c and C57BL/6 mice may exhibit clinical symptoms such as difficulty breathing, weight loss, and ruffled fur, partly depending on the virus strain and inoculum 80 , 83 , 89 .…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that cotton rats are the most permissive small animal model and that peak virus titers occurred at day four post infection 76 78 . Viral lung replication and disease vary between different inbred mouse strains; most work has been published in the BALB/c model, which exhibits substantial disease symptoms 79 88 . BALB/c and C57BL/6 mice may exhibit clinical symptoms such as difficulty breathing, weight loss, and ruffled fur, partly depending on the virus strain and inoculum 80 , 83 , 89 .…”
Section: Animal Modelsmentioning
confidence: 99%
“…The role of natural killer (NK) cells is unclear. One study depleted NK cells with anti-CD49 antibody and reported prolonged viral replication 99 , whereas another depleted NK cells with the more specific antibody anti-NK1.1 and found no effect 88 .…”
Section: Pathogenesis and Immunitymentioning
confidence: 99%
“…Depletion of NK cells with anti-CD49b/Pan-NK cell monoclonal antibody in BALB/c mice resulted in increased lung viral titers on days 7, 28 and 60 after infection compared to NK cell competent mice. In contrast, work reported by Wen S. et al in C57BL/6 mice have demonstrated that NK cells do not contribute to hMPV clearance [ 51 ]. Lung NK cell numbers in infected mice were, however, increased as early as day 1 after hMPV infection and peaked on day 3 compared to mock infected mice.…”
Section: Lung Antiviral and Inflammatory Responsesmentioning
confidence: 93%
“…The role of NK cells in the antiviral response against hMPV infection appears to be mouse strain dependent. In both BALB/c and C57BL/6 mouse strains, NK cells are recruited to the lungs upon hMPV infection [91,92,100,142]. Moreover, the recruited NKs are activated, as indicated by the increased release of cytotoxic granules [100,142].…”
Section: Natural Killer Cells (Nks)mentioning
confidence: 99%